PENINGKATAN HASIL BELAJAR SISWA MELALUI PENERAPAN METODE PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISIONS) - Ratna Indayani (Saintifika, 2021)
Abstract: Science learning in class VII SMP Negeri 4 Jember in the odd semester of the 2019/2020 school year is not optimal because it still uses conventional learning. In order for learning to be more effective and to increase the completeness of learning outcomes, it is necessary to use cooperative learning methods. The research objective was to describe the improvement of student learning outcomes in the material properties of the material through the application of the STAD (Student Teams Achievement Division) type of cooperative learning method. This research is a type of classroom action research (PTK) which includes several cycles with the stages: 1) planning, 2) action, 3) observation, and 4) reflection. The research data was taken through tests in the form of description questions and non-tests in the form of observations and interviews. Furthermore, the data were analyzed descriptively, quantitatively and qualitatively. Based on the results of the research conducted, it was found that there was an increase in student learning outcomes, namely 53.1% in pre-cycle, then 68.8% in cycle I, and increased again to 93.8% in cycle II. Thus the STAD (Student Teams Achievement Division) type cooperative learning method can improve student learning outcomes. Kata Kunci: Learning outcomes, kind of substance, STAD.